Student Perceptions of the Implementation of Green Human Resource Management in Higher Education: Analysis of Determining Factors - Wibowo, Agung; Kusumah, Anuraga; Prasetia, Angga (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to explore students' perceptions of the implementation of Green Human Resource Management (GHRM) in higher education. With increasing awareness of environmental issues, GHRM has become important in the context of higher education. This study used a quantitative approach by distributing questionnaires to students at several universities in Indonesia. The results showed a positive relationship between students' understanding of GHRM and their attitudes toward sustainability. This study also identified determinants that influence students' perceptions, including education, experience, and involvement in environmental activities. This study recommends that universities pay attention to improving education, providing support for students, and creating a supportive organizational environment for students to be more involved in GHRM. These findings are expected to provide insights for universities in developing more effective GHRM policies